16.5k views
5 votes
Y – 5 = x 4x – y = 4 elimination

User Shikkediel
by
5.5k points

2 Answers

4 votes

y - 5 = x

4x - y = 4

Arrange:

y - 5 = x

-x + y = 5

-x + y = 5

4x - y = 4

Add together:

-x + y = 5

4x - y = 4

3x = 9

3x = 9

Solve for x:

x = 9 ÷ 3

x = 3

Substitute and solve y:

y - 5 = x

y - 5 = 3

y = 3 + 5

y = 8

x = 3

y = 8

User Chuck Norris
by
5.5k points
3 votes

Answer:

(3,8)

Explanation:

y - 5 = x

4x - y = 4

Since y-5 = x, substitute y-5 in place of x in the second equation:

4x- y = 4

4(y-5) - y = 4

4y - 4*5 - y = 4

3y - 20 = 4

3y = 24

y =8

Solve for x:

y - 5 = x

8-5 = x

3 = x

Check:

4x - y = 4

4(3) - 8 = 4

12 - 8 = 4

4 = 4

Check

y - 5 = x

8 - 5 = 3

3 = 3

Check!

User Pablo Rincon
by
5.2k points